The Relationship Between Intact Parathyroid Hormone and 25-Hydroxyvitamin D in United Kingdom Resident South Asians and Whites: A Comparative, Cross-Sectional Observational Study - Coley-Grant, Deon; Jawad, Mohammed; Ashby, Helen L.; Cornes, Michael P.; Kumar, Bharan; Hallin, Magnus; Nightingale, Peter G.; Ford, Clare; Gama, Rousseau (Hormone and Metabolic Research, 2021)
Ethnic differences in intact parathyroid hormone (iPTH) at similar total 25 hydroxyvitamin D [25(OH)D] concentrations have been reported between US resident Whites, Blacks, and Hispanics, but this has not been studied between South Asians and Whites. We, therefore, compared the iPTH relationship to 25(OH)D in UK resident South Asians and Whites. A comparative, cross-sectional observational study in which demographic and laboratory data on South Asian and White residents of Wolverhampton, UK were analyzed. Log-log models measured the association between 25(OH)D and the interaction term of ethnicity and iPTH. Seven hundred and seventy-two patients consisting of 315 white subjects (208 women) and 457 South Asian subjects (331 women) were studied. Compared to South Asians, White subjects were older, had higher serum concentrations of 25(OH)D, creatinine (lower eGFR), adjusted calcium and magnesium, but similar concentrations of iPTH and phosphate. In an adjusted model, variables significantly associated with 25(OH)D included age, creatinine, adjusted calcium and ethnicity; but not iPTH and the interaction term of ethnicity and iPTH (beta coefficient –0.071, 95% CI –0.209, 0.067, p=0.32). In our study cohort, iPTH was not, per se, influenced by 25 (OH)D. We found no ethnic differences in the association between iPTH and 25(OH)D between South Asians and White UK residents
Keywords: vitamin D; parathyroid hormone; South Asians; white; ethnicity